Customer satisfaction with regard to night entertainment services and security management focus on Smallville Complex businesses - Antay, Karen Claire; Noble, April Joy; Sale, Joseph John Michael; Trinidad, John Michael
The study focuses on the Smallville complex. The entertainment services and security management are the basis of customer satisfaction with regard to the business establishments in Smallville. The whole study would help customers become aware of their safety in Smallville at night. it would also be useful for managers to help them manage their security and entertainment better for the purpose of their customers and their businesses. Establishments in Smallville include nightclubs, coffee shops and restaurants. Customers are asked about their preferences and their reasons for these. They also gave opinions on entertainment and security which affect their level of satisfaction of the business establishments in Smallville. Managers, owners and supervisors were also asked on factors such as entertainment services provided and how they manage security for the safety of everybody. Results and data based on the analytical framework of the study were collected then analyzed and compared. These showed that most people are contented with the security in Smallville. When it comes to entertainment, many are also satisfied. These are based on the results of the interview of customers and owners, managers and supervisors.